2021
DOI: 10.3390/cells10113221
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Epithelial Stem Cells Counteract Acidic Degradation By-Products of Electrospun PLGA Scaffold by Improving Their Immunomodulatory Profile In Vitro

Abstract: Electrospun poly(lactic-co-glycolic acid) (PLGA) scaffolds with highly aligned fibers (ha-PLGA) represent promising materials in the field of tendon tissue engineering (TE) due to their characteristics in mimicking fibrous extracellular matrix (ECM) of tendon native tissue. Among these properties, scaffold biodegradability must be controlled allowing its replacement by a neo-formed native tendon tissue in a controlled manner. In this study, ha-PLGA were subjected to hydrolytic degradation up to 20 weeks, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
(159 reference statements)
1
7
0
Order By: Relevance
“…Accordingly, the 3D scaffolds’ average diameter size was within the range of that of tendon collagen fibers (1–20 µm) where tenocytes reside [ 44 , 45 , 46 , 47 ]. Similarly to what was previously observed in PLGA fleeces [ 15 , 16 , 17 , 34 ], SEM analyses demonstrated that PLGA 3D scaffolds exhibited a good fiber alignment and arrangement, which could be considered desirable features to mimic tendon morphology [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Accordingly, the 3D scaffolds’ average diameter size was within the range of that of tendon collagen fibers (1–20 µm) where tenocytes reside [ 44 , 45 , 46 , 47 ]. Similarly to what was previously observed in PLGA fleeces [ 15 , 16 , 17 , 34 ], SEM analyses demonstrated that PLGA 3D scaffolds exhibited a good fiber alignment and arrangement, which could be considered desirable features to mimic tendon morphology [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 61%
“…This time span was selected according to previous studies in which it was demonstrated that AECs engineered on highly aligned constructs differentiated towards the tenogenic lineage and modulated IL-10 and IL-12 gene expression profile already after 48 h of culture [ 15 , 16 , 17 ]. As a support, it has been evidenced that 48 h represents the initial time contact between the scaffold and the host tissue, as well as, the early inflammatory phase of tendon healing [ 26 , 34 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSCs are pluripotent non-hematopoietic adult stem cells generated from the germinal layer of mesoderm ( Pillai et al, 2017 ). The MSCs can be found in bone marrow, adipose, periosteum, skin, blood vessel walls, tendons, muscles, peripheral circulation, umbilical cord blood, periodontal ligament, and tooth tissue ( Wang et al, 2013 ; Chen J. et al, 2021 ; El Khatib et al, 2021 ). A range of active molecules (e.g., BMP-12/7 and growth factor) can promote further expansion and tendinogenic differentiation ( Tang and Lane, 2012 ; Zhou et al, 2019a ; Perucca Orfei et al, 2019 ).…”
Section: Tissue Regeneration Strategies For Achilles Tendon Injury Tr...mentioning
confidence: 99%